Circular economy as an approach to sustainability and its impact on the environment : DOI: 10.5937/etp2503071V - Vasić, Stana; Ristić, Kristina; Vasić Garić, Milica (Ekonomija - teorija i praksa, 2025)
The concept of circular economy (CE) has become a key framework for achieving sustainability through the efficient use of resources, waste minimization, and material recirculation. This study presents a systematic literature review encompassing scientific papers published between 2015 and 2025, with the aim of examining how circular economy practices affect the environment. The analysis focuses on the most frequently applied methodological approaches, including Life Cycle Assessment (LCA), Material Flow Analysis (MFA), and carbon footprint assessment, as well as on indicators applied at the micro, meso, and macro levels. The results indicate a lack of methodological standardization and a limited connection between the environmental, economic, and social dimensions of sustainability. Although the circular economy shows potential for reducing material and energy consumption, the comparability of results remains limited due to the heterogeneity of indicators. This paper contributes to the existing literature by identifying key methodological gaps and proposing the inclusion of digital technologies, data transparency, and harmonized policies as priorities for future research and implementation